2015
DOI: 10.20533/ijtie.2047.0533.2015.0090
|View full text |Cite
|
Sign up to set email alerts
|

Gifted amongst Preschool Children An Analysis on How Teachers Recognize Giftedness

Abstract: The aim of this research is to expose what teachers from two different cultures observe as characteristics of giftedness in preschool children. The research also depicts the teachers' conception of inclusive gifted education. The applied qualitative methodology is based in an interview, which focuses on understanding teachers' difficulties and perceptions in identifying and recognizing a gifted preschool child. Eight teachers, from Brazil and Portugal, participated in this study. Teachers' answers were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The study of which features potentially intervene in the presence of high capabilities for development in children was the first step in this research. For this purpose, pedagogical and sociological research was taken into account [3][4][5]8,16], as well as the professional experience of teaching personnel at the preschool level. In addition, other situations that may influence detection such as environmental and socioeconomic factors were analyzed [2].…”
Section: The Kindergarten Children Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The study of which features potentially intervene in the presence of high capabilities for development in children was the first step in this research. For this purpose, pedagogical and sociological research was taken into account [3][4][5]8,16], as well as the professional experience of teaching personnel at the preschool level. In addition, other situations that may influence detection such as environmental and socioeconomic factors were analyzed [2].…”
Section: The Kindergarten Children Datamentioning
confidence: 99%
“…Children with high development potential need specific learning strategies so that their development can be enhanced [1][2][3]. Cuban pedagogy wagers on teaching styles that respect individual differences and grant each child the ability to assimilate knowledge at his or her own pace, in a personalized way and according to each individual's needs.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, nonetheless, teachers noted specific intellectual abilities that they found significantly advanced among gifted children. These include strong reasoning skills, a broad fund of knowledge, a wide vocabulary (Moon and Brighton, 2008), reading skills and reading comprehension, problem-solving, attention and memory, speed in processing, and creativity (Ogurlu and Çetinkaya, 2012;Dal Forno et al, 2015;Yazici et al, 2017). Teachers believe that these competencies were developed experientially in stimulating home environments.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, nonetheless, teachers noted specific intellectual abilities that they found significantly advanced among gifted children. These include strong reasoning skills, a broad fund of knowledge, a wide vocabulary ( Moon and Brighton, 2008 ), reading skills and reading comprehension, problem-solving, attention and memory, speed in processing, and creativity ( Ogurlu and Çetinkaya, 2012 ; Dal Forno et al, 2015 ; Yazici et al, 2017 ). Teachers believe that these competencies were developed experientially in stimulating home environments.…”
Section: Introductionmentioning
confidence: 99%